[OA027] Helium as a range probe in carbon ion therapy. (August 2018) - Graeff, Christian; Weber, Uli; Schuy, Christoph; Saito, Nami; Volz, Lennart; Piersimoni, Pierluigi; Seco, Joao; Kraemer, Michael
Abstract : Purpose: Range uncertainty is a major uncertainty in particle therapy, especially in extracranial irradiations. As helium has the same magnetic rigidity but more than twice the range at the same velocity as carbon, it is in principle possible to mix beams, using carbon for therapy while simultaneously detecting Helium exiting the patient to assess beam range. Methods: To investigate feasibility, a single field irradiation was simulated on a lung cancer patient using the GSI in-house TPS TRiP98, using a field consisting of 90% carbon and 10% helium. Target dose was optimized to 2 Gy(RBE), taking into account dose from both ions but keeping the ratio constant. The 10% helium deposited less than 0.5% of the target dose while passing through the patient, notably also less than the Carbon fragment tail within the patient. Results: The maximum energy in this patient was 255 MeV/u, corresponding to ranges of 12.8 and 39.2 cm H2O for helium and carbon, respectively. In the pencil beam dose algorithm, a dose of approximately 1 cGy was calculated in the Bragg Peak region of helium. In order to detect helium ions beyond the patients, secondary nuclear fragments must be separated from primary helium ions. For the lowest energies, carbon and helium delivered approximately the same dose, but carbon dose fell below 1 mGy 10 cm before the distal range of helium. Individual Bragg Peaks of helium were clearly separable in water due to the relatively larger spacing of carbon energies determining the energy layout of the plan. Conclusions: MC simulations and experiments are needed to study the best combination of simultaneous Carbon-therapy and Helium-imaging. Fast detection systems could be used to check ranges online, while position-sensitive detectors would permit ion radiography before or during therapy. Here, single particle tracking techniques as developed for proton imaging would benefit from the lesser scattering of helium. In moving tumors, range-based motion detection or gating could be possible, especially in the lung with large density differences of tumor and lung.